The Argentine Economy under the Dictatorship: From Inflation to Carry Trade, from the Dollar to Plata Dulce - Luzzi, Mariana (Hispania Nova, 2026)
How did the military dictatorship reshape the Argentine economy? For more than half a century, this question has been answered primarily in macroeconomic terms. The restructuring of the local economy promoted by the military left behind a dismantled industry, a more unequal social structure and an enormously multiplied public foreign debt. However, the effects of this reform program were not limited to the economic structure. Household economic practices were also affected, as a result of the combination of the state’s deregulatory impulse with the conditions created by continuing economic problems and longer-term trends. One expression of these changes was the growing importance of the financial system for household economies; the other was the incorporation of the dollar into various markets and into the financial repertoires of different social groups. This article focuses on the analysis of both processes.